(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What is the syntaxonomical position of the acidophilous forest edges on Kyiv Polissia? Location: Kyiv city; Buchanskyi and Vyshhorodskyi administrative districts of Kyiv Region, Ukraine. Methods: A local dataset of 14 vegetation plots stored in the database created by Turboveg software and analyzed using the modified TWINSPAN algorithm within JUICE 7.1 software, is used. For comparison, a shortened synoptic table containing an additional 105 phytosociological relevés from 6 literature sources was performed. Ecological conditions of the distinguished communities were estimated using Ellenberg Indicator Values. Nomenclature: https://europlusmed.org, Hodgetts et al. 2020, https://indexfungorum.org), Mucina et al. 2016. Results. On Kyiv Polissya, acidophilous forest edges pose a significant share of Euro-Siberian and East-European psammophytic xeromesophytic taxa (Cytisus ruthenicus var. zingeri, Psephellus sumensis, Veronica spicata var. pseudoorchidea). At the same time, these communities are built mainly by wide-range mesotrophic and oligotrophic subacidophilic species, common also with subatlantic forest edges (Agrostis capillaris, Festuca ovina, Hieracium umbellatum, Melampyrum pratense, Peucedanum oreoselinum, Veronica officinalis). In the study area, a new association Veronico spicatae-Melampyretum pratensis is described, connected with the margins and glades of subcontinental preboreal pine forests on sandy acidic soils. On the edges of acidophilous oak forests in the southern part of the region, the community Hieracium murorum-Agrostis capillaris is distinguished. In the study, we postulate and prove that such forest-edge communities belong to the Melampyrion pratensis alliance. Conclusion. The results of the study complement the understanding of the diversity of Trifolio-Geranietea sanguinei class in Ukraine and clarify views on the geographical distribution of the Melampyrion pratensis alliance in Eastern Europe.